Closed reduction and percutaneous fixation of sacroiliac luxations in cats using 2.4 mm cannulated screws – a cadaveric study - Fischer, A.; Binder, E.; Reif, U.; Biel, M.; Bokemeyer, J.; Kramer, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2012)
Objectives: To describe fluoroscopically assisted percutaneous placement of 2.4 mm cannulated screws for fixation of artificially induced sacroiliac luxations in cats, and to evaluate the success of this technique in restoration of normal pelvic anatomy.Methods: Fluoroscopically assisted closed reduction and percutaneous fixation of sacroiliac luxations using 2.4 mm cannulated screws was performed in cadavers of 12 cats. Pre- and postoperative radiographs and postoperative computed tomographic scans were used to evaluate screw placement, screw purchase within the sacral body, reduction of the sacroiliac joint, pelvic canal diameter ratio, and hemipelvic canal width ratio.Results: Mean total surgical time was 6 minutes and 10 seconds ± 53 seconds and mean total time of fluoroscopic screening for each procedure was 44 seconds ± 6 seconds. Mean percent of reduction was 98.33% and mean screw purchase within the sacral body was 73%. Eleven out of 12 screws were placed in a satisfactory location in the sacral body. Pelvic canal diameter ratio and hemipelvic canal width ratio indicated successful restoration of the pelvic anatomy.Clinical significance: Our results confirm that fluoroscopically assisted percutaneous placement of 2.4 mm cannulated screws is a feasible technique for fixation of sacroiliac luxations in cats. Mechanical properties of this fixation technique need to be evaluated before the use in clinical patients.
Keywords: Sacroiliac luxation; cannulated screw; cat